Postmortem Neuroimaging of Cetacean Brains Using Computed Tomography and Magnetic Resonance Imaging - Kot, Brian C. W.; Tsui, Henry C. L.; Chung, Tabris Y. T.; Lau, Amy P. Y. (Frontiers in Marine Science, 2020)
In the course of the pioneering virtopsy-driven cetacean stranding response program in the Hong Kong waters, postmortem computed tomography (PMCT) and postmortem magnetic resonance (PMMR) imaging (PMMRI) have been implemented to provide supplementary or complementary information for conventional necropsy. Stranded carcasses are often badly degraded and susceptible to rapid cerebral autolysis and putrefaction. Necropsy on decomposed brains with limited sample analysis often defy a specific diagnosis. Studies on PMMR neuroimaging have been focused on neuroanatomy and brain morphology in freshly deceased or preserved specimens. The literature is devoid of any reference on the potential value of PMMRI examination of decomposed cetacean brains. This project evaluated the benefits of PMMR neuroimaging in situ in decomposed carcasses in comparison to PMCT. A total of 18 cetacean carcasses were studied by PMCT and PMMRI examinations. Anatomical brain structures and visible brain pathologies were evaluated and scored using Likert-scale rating. Intracranial gas accumulation was clearly depicted in all cases by all radiological techniques. Other features were more clearly depictable in PMMRI than in PMCT images. The results of the present study indicated that superiority of PMMRI compared to PMCT increased with advancing putrefaction in brain. The preservation of structural integrity was visualized by PMMRI due to its superior ability to depict soft tissue. PMMRI brain should be incorporated in postmortem investigation of decomposed stranded cetaceans.